HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA DALAM PENCEGAHAN PENULARAN HIV/AIDS TERHADAP KETERPAPARAN MEDIA MASSA DI SMA SWASTA RAKSANA MEDAN - Deviana Pratiwi Munthe (STIKes Mitra Husada Medan, 2018)
HIV/AIDS case in adolescents is increasing; until 2015 there were 2,030 people suffering from HIV/AIDS because adolescents’ knowledge and attitude toward HIV/AIDS were low. The objective of the research was to find out the correlation of adolescents’ knowledge and attitude toward HIV/AIDS infection on exposure to mass media. The research used an analytic survey method with cross sectional design. The population was 406 Grades X and XI students at SMA Swasta Raksana Medan, and 143 of them were used as the samples, taken by using simple random sampling technique. The data were gathered by distributing questionnaires and analyzed by using chi square test. The result of the research showed that there was significant correlation between the exposure of mass media and adolescents’ knowledge of forestalling HIV/AIDS infection at p-value = 0.001. There was significant correlation between the role of peers and adolescents’ knowledge (p=0.047) and attitude (p=0.026) in forestalling HIV/AIDS infection.It is recommended that the school management provide reading books, making website on HIV/AIDS and establish counselor to discuss infection and forestalling HIV/AIDS, collaborating with LSM, the Health Agency, KPAN, and BKKBN as the facilitators so that students will get correct information about HIV/AIDS. Keywords: Mass Media, Knowledge, Attitude, Forestalling, Infection, HIV/AIDS